Perancangan dan Implementasi Human Resource Information System (HRIS) - Martono Martono (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2026)
The Human Resource Department (HRD) plays a very important role in supporting the growth and sustainability of an organization or company. Employees represent the most valuable asset owned by the company, which means that HRD can be considered the most critical component that must be managed properly. The primary function of HRD encompasses the management of all aspects related to the workforce, including ensuring that every employee fully receives their rights. To enhance work effectiveness and efficiency, HRD requires support in the form of a computer-based technology system. Therefore, it is necessary to develop an application capable of accelerating and simplifying employee data management. This study aims to improve HRD performance through the creation of a Human Resource Information System (HRIS). The application development process adopts the Waterfall method. The final outcome of this research is an application that successfully facilitates the HRD department in carrying out its various tasks more effectively.